Resistência parasitária no uso de vermífugos em bovinos de corte no Brasil - Aguiar, Valléria Moreira (Universidade Federal do Tocantins, 2023)
The activities that integrated the mandatory curricular internship, which started on March 07, 2022 and ended on May 16, 2022, were carried out at J. A. Saúde Animal, in Araguaína-TO, directed to the commercial area, totaling 390 hours. It was supervised by the Veterinary Doctor Guaraci Reis de Lima and supervised by Prof. Dr. Fabiana Cordeiro Rosa. During the internship, technical visits were done to rural properties and agricultural houses, where consultations were carried out in order to generate demands for the commercialized products, in addition to a whole training support. Parasitic resistance is a disease that affects many farms, decreasing productivity and profits. It is extremely important to obtain knowledge about the methods necessary to avoid it, as prevention generates less expenses than treatments. There are several treatments on the market, requiring a technical evaluation to obtain favorable results for the specific cause that affects the property.